Is the USSR Superior to the West as A Market for Primary Products? - Neuberger, Egon (The Review of Economics and Statistics, 1964)
Soviet spokesmen have claimed repeatedly that the USSR is an ideal market for primaryproduct exports of underdeveloped countries. The markets of leading western industrial countries, on the other hand, are said by the Soviets to be extremely unsatisfactory due to the chaos and stagnation allegedly inherent in the capitalist system. The purpose of this paper is to assess the validity of these Soviet claims by comparing the relative performance of the USSR and leading western industrial countries as markets for primary products in the period 1955 to 1961. The method used is one which tests whether Soviet primary product imports were larger, more rapidly growing, and more stable than western imports. This comparison is based entirely on available official foreign trade statistics of each country.